The use of content and timing to predict turn transitions - Garrod, Simon; Pickering, Martin J. (Frontiers in Psychology, 2015)
For addressees to respond in a timely fashion, they cannot simply process the speaker’s utterance as it occurs and wait till it finishes. Instead, they predict both when the speaker will conclude and what linguistic forms they will use. While doing this, they must also prepare their own response. To explain this, we draw on the account proposed by Pickering and Garrod (2013a), in which addressees covertly imitate the speaker’s utterance and use this to determine the intention that underlies their upcoming utterance. They use this intention to predict when and how the utterance will end, and also to drive their own production mechanisms for preparing their response. Following Arnal and Giraud (2012), we distinguish between mechanisms that predict timing and content. In particular, we propose that the timing mechanism relies on entrainment of low-frequency oscillations between speech envelope and brain. This constrains the context that feeds into the determination of the speaker’s intention and hence the timing and form of the upcoming utterance. This approach typically leads to well-timed contributions, but also provides a mechanism for resolving conflicts, for example when there is unintended speaker overlap.